A Proposition and an Example in the Theory of Job Search with Hours Constraints - Kiefer, Nicholas M. (Journal of Labor Economics, 1987)
This paper considers wage-hours contracts in the context of a jobsearch model. The response of a risk-averse worker to a wage translation of the offer distribution is examined. A robust example illustrates that some "natural" results need not hold.